The Community Health and Social Medicine Incubator: a service-learning framework for medical student-led projects (Canadian Medical Education Journal, 2021)
Implication StatementThe Community Health and Social Medicine (CHASM) Incubator is a social impact venture that gives medical and other health care students the opportunity to develop initiatives that sustainably promote health equity for, and in partnership with, community partners and historically marginalized communities. Students learn how to develop projects with project management curricula, are paired with community health mentors, and are given seed micro-financing. As the first community health incubator driven by medical students, CHASM provides a framework for students interested in implementing sustainable solutions to local health disparities which extends the service-learning opportunities offered in existing curricula.